Developing The Capacity For Collaborative, Need-Focused And Action-Oriented Research In Community Schools In Nigeria (Journal of Pharmaceutical Negative Results, 2023)
The study partly presented in this paper covered a collaborative and innovative research project that brought together higher education, K-12 educators, and administrators as well as community (leaders and parents) to plan for change through an emergent qualitative design approach. Using an iterative process, the co-researchers cross-trained and queried themselves about the needs of community schools in the vicinity of a premier Nigerian University, identifying areas of success and disconnection. First level of data pointed to resource needs such as libraries. Further data collection from diverse stakeholders elicited the involvement of non-profits and governmental bodies to institute the creation of libraries as centers of civic engagement, to further school and community bonds. This ongoing collaborative project has potential to foster much-needed change in typically under-resourced Nigerian schools while creating necessary philanthropic engagement, meaningful curriculum changes, efficacious administrative leadership, and robust higher education research. A final promise is to network with researchers across the U.S. and Nigeria.